Experimental investigation of top compression piston ring morphology for hydrogen enrichment diesel engine - Md. Nafiah, Mohd Rozaini (2016)
Many researchers believe hydrogen-diesel engine will have an expanded role in the future. Hydrogen-diesel engine generally have reduced vehicle emissions which contribute to smog, air pollution and global warming. Besides that hydrogen-diesel engine also can improve diesel engine thermal efficiency. Hydrogen was produced by electrolysis process and supplied via natural aspirated air flow to the combustion chamber. However hydrogen-diesel combustion causes severe effects to engine components longevity. The component such as piston ring was exposed to high flame combustion under hydrogen enrichments which cause its mechanical material properties to changes. The paper presents an experimental investigation of the morphological effects on top compression piston ring of single cylinder diesel engine under hydrogen enrichments combustion. Scanning Electron Microscopy (SEM) and Energy Dispersive Spectrometer (EDS) test was performed to observe the microstructure changes on the coating surface of compression piston ring before and after hydrogen enrichment combustion. Another technique of imaging used was Focus Ion Beam (FIB) Dual Beam machine to observe the hydrogen embrittlement affect up to 30 μm depth inside the samples coating. Finally, three point bending test using Universal Tensile Test (UTS) machine was performed to get comparative flexural bending strength and flexural modulus for sample before, under normal diesel engine condition, after hydrogen enrichment diesel combustion, nano homogeneus and none-homogeneus engine oil. The results from experiments showed that hydrogen embrittlement caused the coating surface peeled off seriously and also induced a lot of microstructure crack inside the coating layer of top compression piston ring. As the results, top compression piston ring flexural strength and ductility have reduced drastically. The piston ring failure will increased the friction with cylinder. wall ~d this problem can cause catastrophic damage on the engine such as overheating. Surface treatment or special coating is needed to improve the piston ring capability to overcome the hydrogen enrichment diesel combustion.